Post-COVID-19 syndrome symptoms after mild and moderate SARS-CoV-2 infection - Al-Husinat, Lou’i; Nusir, Mokeem; Al-Gharaibeh, Haitham; Alomari, Amer A.; Smadi, Mahmoud M.; Battaglini, Denise; Pelosi, Paolo (Frontiers in Medicine, 2022)
Background Post-COVID-19 Syndrome (PCS) is characterized by residual symptoms following the initial recovery from severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. The prevalence of PCS is known to be the highest among severe and critical forms of the disease. However, the occurrence and risk factors for PCS after mild or moderate SARS-CoV-2 infection has not been extensively investigated. Methods Online and offline via both paper or mailed questionnaires distributed among Jordan collected between 1st and 21st August 2021, including a total number of 800 respondents, of whom 495 had previous mild to moderate COVID-19 infection. The Newcastle post-COVID syndrome Follow-up Screening Questionnaire was modified, translated, and used as a standard instrument for data collection regarding psychological, medical, and socio-economic symptoms post-infection. The primary outcome was the prevalence of PCS after mild to moderate COVID-19 in Jordan. Secondary outcome was the identification of PCS risk factors. Results The most common PCS symptom was mood disturbance followed by fatigue, anxiety, and myalgia. Female gender significantly increased the risk for multiple PCS symptoms. Age < 30 years was found to be an independent risk factor for myalgia (p = 0.001). Conclusion PCS is highly prevalent among COVID-19 survivors in Jordan, especially in females and patients with comorbidities. Planning physical and mental rehabilitation services is recommended for those patients with PCS symptoms after mild to moderate COVID-19 infection.